Assessment of the Prevalence of Chronic Backache as a Complication Post-Dural Puncture - Masood Wazir; Farah Ahmad; Syed Tameem ul Hassan; Abbas Khan; Saima Masood; Larayeb Wazir (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Spinal anesthesia is commonly selected for surgical procedures involving the lower abdomen, pelvis, and lower extremities, such as anorectal, urologic, obstetric, and gynecologic surgeries, due to its effectiveness in providing regional anesthesia in these specific areas. Backache is frequently reported after the spinal anesthesia. Studies consistently show that the prevalence of backache after spinal anesthesia is significant in developing countries, although there are also contradictions. Aim: To establish a connection between backache and spinal anesthesia. Methodology: Prospective observational study was conducted inTertiary Care Hospital, KPK, Kohat Pakistan from 1st May 2022 to 31st July 2023. Three hundred and forty-eight patients were enrolled. Numerical rating scale for pain was used to record backache status and a structured questionnaire was used to explore other considerations. Results: There were 26(7.47%) males and 322(92.53%) females with mean age of 30.37±9.00 years. Two hundred and ninety- three (84.20%) patients had no comorbidities while 55 patients (15.80%) had comorbid conditions. Post-dural backache was observed in 234 patients (67.24%) patients. Among male population, 4(15.38%) patients out of 26 patients have developed chronic backache and 206(63.98%) patients out of 322 have developed chronic backache among females. The severity of backache was measured baseline and at one, three, and six months postoperatively with mean NRS scores of 0.45±1.63 immediately, 3.14±2.14 at one month, 2.74±1.54 at three months, and a score of 2.57±1.79 at six months. Immediately after the procedure, 18 patients (5.17%) reported backache. At 1st and 3rd month, 220 patients (63.22%) experienced backache, a number that remained consistent from 1st to 3rd month. After 6 months, the incidence slightly decreased to 210 (60.34%) patients. Practical Implication: Post-dural backache is a significant issue, especially among females, requiring targeted postoperative management and preventive strategies. Healthcare providers should implement early interventions like physical therapy and pain management protocols, especially within the first six months. Conclusion: The high prevalence of post-dural backache among patients undergoing spinal anesthesia in our society, with a significant portion of the patients experiencing chronic backache postoperatively. The severity of backache slightly decreased over a six-month period. These findings emphasize the need for careful monitoring of chronic backache in patients receiving spinal anesthesia. Keywords: Chronic Backache, Post Dural Puncture Backache, Spinal Anesthesia